Apolipophorin-II/I Contributes to Cuticular Hydrocarbon Transport and Cuticle Barrier Construction in Locusta migratoria - Zhao, Yiyan; Liu, Weimin; Zhao, Xiaoming; Yu, Zhitao; Guo, Hongfang; Yang, Yang; Zhang, Jianqin; Moussian, Bernard; Zhang, Jianzhen (Frontiers in Physiology, 2020)
Apolipophorins are carrier proteins that bind lipids and mediate their transport from tissue to tissue in animals. Apolipophorin I and II (apoLp-II/I) are the major apolipophorins in insects. The implication of apoLp-II/I in cuticle lipid-barrier formation in insects has not been addressed to date. In the present study, we investigated the function of apoLp-II/I in the migratory locust Locusta migratoria (LmapoLp-II/I). During the development of fifth instar nymphs, LmapoLp-II/I transcript levels increased until mid-instar, and then decreased gradually until molting to the adult stage. We found that LmapoLp-II/I was predominately expressed in the fat body and the integument including oenocytes and epidermal cells. Immunodetection experiments revealed that LmapoLp-I mainly localized in the cytoplasm of oenocytes and epidermal cells. Silencing of LmapoLp-II/I caused molting defects in nymphs. Importantly, RNAi against LmapoLp-II/I resulted in a significant decrease in the content of cuticle surface lipids including alkanes and methyl alkanes. Cuticular permeability was significantly enhanced in these nymphs in Eosin Y penetration assays. By consequence, desiccation resistance and insecticide tolerance of dsLmapoLp-II/I-treated locusts were reduced. Taken together, our results indicate that LmapoLp-II/I is involved in the transport and deposition of surface-cuticular lipids that are crucial for maintaining normal cuticle barrier function in L. migratoria.